On the Use and Misuse of UML- Application of Diagrams in Engineering - Müller, Wolfgang (Proceedings of the UML for SoC Design Workshop at DAC'07)

Using Smart Cards for Secure and Device Independent User Interfaces - Schäfer, Robbie; Müller, Wolfgang; Marin-López, Andrés; Díaz-Sánchez, Daniel (Proceedings of the International Conference on Mobile Technology, Applications and Systems (Mobility 2007))
Smart Cards are becoming a ubiquitous means for securing a wide range of interactive applications. However in many cases its use is limited for authentication purposes only. In this paper we extend the use of smart cards for carrying abstract user interface descriptions which can be rendered on dierent and potentially remote clients that in addition can support varying interaction modalities. This adds on the one hand to the security since a backend application cannot be used without the UI description, and on the other hand to the versatility of applications, since all devices with a respective renderer for certain modalities can be utilized.

Das Paradigma des Pikaresken - The Paradigm of the Picaresque

Thinking Northern: Textures of Identity in the North of England

The Influence of Catalyst's Oxidation Degree on Carbon Nanotube Growth as a Substrate-Independent Parameter - de los Arcos de Pedro, Maria Teresa; Oelhafen, Peter; Thommen, Verena; Mathys, Daniel (The Journal of Physical Chemistry C)

Optical characterization of alignment and effective refractive index in carbon nanotube films - de los Arcos de Pedro, Maria Teresa; Oelhafen, P; Mathys, D (Nanotechnology)

An Efficient Optical Method to Detect Phase Transitions in Liquid Crystals - Strauß, Jochen; Hoischen, Andreas; Kitzerow, Heinz-Siegfried (Molecular Crystals and Liquid Crystals)
Keywords: Condensed Matter Physics; General Materials Science; General Chemistry

Dual-Frequency Addressable Gratings Based on Polymer-Dispersed Liquid Crystals - Kitzerow, Heinz-Siegfried (Molecular Crystals and Liquid Crystals Science and Technology. Section A. Molecular Crystals and Liquid Crystals)
Keywords: Condensed Matter Physics

Tuneable photonic crystals obtained by liquid crystal infiltration - Kitzerow, Heinz-Siegfried; Lorenz, A.; Matthias, H. (physica status solidi (a))
Keywords: Materials Chemistry; Electrical and Electronic Engineering; Surfaces; Coatings and Films; Surfaces and Interfaces; Condensed Matter Physics; Electronic; Optical and Magnetic Materials

Dichroic photo- and electroluminescence of oligo p-(phenylene vinylene) derivatives - Lauhof, Marcus W.; Benning, Stephan A.; Kitzerow, Heinz-Siegfried; Vill, Volkmar; Scheliga, Felix; Thorn-Csányi, Emma (Synthetic Metals)
Keywords: Materials Chemistry; Metals and Alloys; Mechanical Engineering; Mechanics of Materials; Condensed Matter Physics; Electronic; Optical and Magnetic Materials

Coherent digital polarization diversity receiver for real-time polarization-multiplexed QPSK transmission at 2.8 Gb/s - Pfau, Timo; Peveling, Ralf; Hauden, Jerome; Grossard, Nicolas; Porte, Henri; Achiam, Yaakov; Hoffmann, Sebastian; Ibrahim, Selwan K.; Adamczyk, Olaf; Bhandare, Suhas; Sandel, David; Porrmann, Mario; et al. (IEEE PHOTONICS TECHNOLOGY LETTERS)

PDL-tolerant real-time polarization-multiplexed QPSK transmission with digital coherent polarization diversity receiver - Pfau, T.; Peveling, R.; Hoffinann, S.; Bhandarel, S.; Ibrahim, S.; Sandel, D.; Adamczyk, O.; Porrmann, M.; Noé, Reinhold; Achiam, Y.; Schlieder, D.; Koslovsky, A.; et al. (2007 DIGEST OF THE LEOS SUMMER TOPICAL MEETINGS)

Distributed PMD compensator in Lithium-Niobate-Tantalate: Performance Modeling toward highest bit rates - Bhandare, Suhas; Noé, Reinhold (JOURNAL OF LIGHTWAVE TECHNOLOGY)

100 km fiber span in 292 km, 2.38 Tb/s (16 x 160 Gb/s) WDM DQPSK polarization division multiplex transmission experiment without Raman amplification - Abas, Ahmad Fauzi; Hidayat, Ariya; Sandel, David; Milivojevic, Bijana; Noé, Reinhold (OPTICAL FIBER TECHNOLOGY)

Realtime optical synchronous QPSK transmission with DFB lasers - Pfau, T.; Adamezyk, O.; Herath, V.; Peveling, R.; Hoffmann, S.; Porrmann, M.; Noé, Reinhold (2007 DIGEST OF THE LEOS SUMMER TOPICAL MEETINGS)

Real-time digital carrier & data recovery for a synchronous optical quadrature phase shift keying transmission system - Noé, Reinhold; Pfau, Timo; Adamczyk, Olaf; Peveling, Ralf; Herath, Vijitha; Hoffmann, Sebastian; Porrmann, Mario; Ibrahim, Selwan K.; Bhandare, Suhas (2007 IEEE/MTT-S INTERNATIONAL MICROWAVE SYMPOSIUM DIGEST, VOLS 1-6)

Liquid crystal director fields in micropores of photonic crystals - Matthias, Heinrich; Schweizer, Stefan L; Wehrspohn, Ralf B; Kitzerow, Heinz-Siegfried (Journal of Optics A: Pure and Applied Optics)
Keywords: Atomic and Molecular Physics; and Optics

Real-time Digital Carrier & Data Recovery for a Synchronous Optical Quadrature Phase Shift Keying Transmission System - Noé, Reinhold; Pfau, Timo; Adamczyk, Olaf; Peveling, Ralf; Herath, Vijitha; Hoffmann, Sebastian; Porrmann, Mario; Ibrahim, Selwan K.; Bhandare, Suhas (2007 IEEE/MTT-S International Microwave Symposium)

Distributed PMD Compensator in Lithium–Niobate–Tantalate: Performance Modeling Toward Highest Bit Rates - Bhandare, Suhas; Noé, Reinhold (Journal of Lightwave Technology)

Coherent Digital Polarization Diversity Receiver for Real-Time Polarization-Multiplexed QPSK Transmission at 2.8 Gb/s - Pfau, Timo; Peveling, Ralf; Hauden, JÉrÔme; Grossard, Nicolas; Porte, Henri; Achiam, Yaakov; Hoffmann, Sebastian; Ibrahim, Selwan K.; Adamczyk, Olaf; Bhandare, Suhas; Sandel, David; Porrmann, Mario; et al. (IEEE Photonics Technology Letters)

Kastrat - Grotjahn, Rebecca (Enzyklopädie der Neuzeit Bd. 6)

Das Elend der Sozialen Arbeit – Die „neue Unterschicht“ und die Schwächung des Sozialen - Heite, Catrin; Klein, Alex; Landhäußer, Sandra; Ziegler, Holger (Erziehung zur Armut? Soziale Arbeit und die ‚neue Unterschicht’)
Die 'neue Unterschicht' ist entdeckt und die Erziehung dieser prekarisierten Gesellschaftsmitglieder wird gefordert. FachexpertInnen aus Erziehungswissenschaft und Sozialpädagogik gehen in diesem Band der Frage nach, wie angemessen eine solche Diagnose der 'neuen Unterschicht' und der damit verbundene Therapievorschlag einer Erziehung zur Armut ist: Wie wird hier soziale Ungleichheit in einer veränderten Form zum Gegenstand? Welche Herausforderungen sind damit für die Soziale Arbeit verbunden? Hält die Diagnose einer 'neuen Unterschicht' einer empirischen Überprüfung stand? In welcher Weise werden hier bestimmte Bevölkerungsgruppen zum Zielpunkt politischer Strategien? Die Beantwortung dieser Fragen macht das Spannungsverhältnis struktureller, kultureller und moralischer Erklärungsversuche mit Blick auf eine fachliche und politische Verortung Sozialer Arbeit analysierbar.
Keywords: Bildung Gesellschaft Moral Soziale Arbeit Sozialpädagogik Sozialstaat Unterschicht neue Unterschicht

"Antlitz der Zeit". Zur soziologisch-politischen Dimension des Physiognomischen in der Ära der Neuen Sachlichkeit - Öhlschläger, Claudia (Die Souveränität der Literatur. Zum Totalitären der Klassischen Moderne 1900-1933)

Middleware for Secure Home Access and Control - Marin, Andres; Müller, Wolfgang; Schäfer, Robbie; Almenarez, Florina; Diaz, Daniel; Ziegler, Max (Proc. of the IEEE PerCom Middleware Support for Pervasive Computing (PerWare 2007))
User adaptive systems in the context of pervasive computing can only unveil their power if based on a generic middleware managing private data and context information in combination with flexible device access and control. However, managing those data poses severe privacy problems both legally and from a trust perspective. Therefore we propose a home automation middleware for secure management of user and context data that gives access to services just for the authorized users and devices. The middleware has been successfully tested at the ambient computing (AC-LAB) at the University of Paderborn.

Device Independent User Interfaces for Smart Cards - Schäfer, Robbie; Müller, Wolfgang; Marin-López, Andrés; Díaz-Sánchez, Daniel (Proceedings of the 9th International Conference on Human Computer Interaction with Mobile Devices and Services (MobileHCI2007))
Smart Cards are becoming a ubiquitous means for securing a wide range of interactive applications. However in many cases its use is limited for authentication purposes only. In this paper we extend the use of smart cards for carrying abstract user interface descriptions which can be rendered on different and potentially remote clients that in addition can support different interaction modalities. This adds on the one hand to the security since a backend application cannot be used without the UI description, and on the other hand to the versatility of applications, since all devices with a respective renderer for certain modalities can be utilized.
Keywords: Smart Card; Abstract User Interface; Device Independence

A Low-Cost Positioning System for Location-Aware Applications in Smart Homes - Schäfer, Robbie; Müller, Wolfgang; Deimann, Roman; Kleinjohann, Bernd (Proceedings of the Workshop on Mobile Spatial Interaction at CHI 2007)
Location-aware services for private use such as GPS- based navigation systems and GSM-based offerings have become quite a success for outdoor applications, while indoor positioning systems are still mainly employed for professional use only. The main reasons are cost issues and the complexity of setup and maintenance of those systems. In this paper we present CaMPTrack (Camera-based Multiple Person Tracker), a prototype of a webcam-based positioning system and discuss its application and development challenges.
Keywords: Positioning Systems; Camera Based; Cost Efficiency; Smart Home Applications

Evaluation of a Multimodal System Based on Dialogue Models and Transformations International Workshop on Usability of User Interfaces: From Monomodal to Multimodal - Schäfer, Robbie; Müller, Wolfgang (Proceedings of IWUMUI’2007 at HCI'2007)

Tuneable photonic crystals obtained by liquid crystal infiltration - Kitzerow, Heinz-Siegfried; Lorenz, A.; Matthias, H. (physica status solidi (a))
Keywords: Materials Chemistry; Electrical and Electronic Engineering; Surfaces; Coatings and Films; Surfaces and Interfaces; Condensed Matter Physics; Electronic; Optical and Magnetic Materials

Optoelectronic and photonic properties of liquid crystals: electroluminescence and photorefractivity - Benning, Stephan A.; Lauhof, Marcus W.; Paelke, Lutz; Redler, Andreas; Scheliga, Felix; Thorn-Csanyi, Emma; Vill, Volkmar; Kitzerow, Heinz-Siegfried (SPIE Proceedings)

Stabilization of bi‐linear mixed finite elements for tetrahedra with enhanced interpolation using volume and area bubble functions - Mahnken, Rolf; Caylak, Ismail (International Journal for Numerical Methods in Engineering)

Two mixed finite element formulations with area bubble functions for tetrahedral elements - Mahnken, Rolf; Caylak, Ismail; Laschet, Gottfried (Computer Methods in Applied Mechanics and Engineering)

Simulation of asymmetric effects for shape memory alloys using the concept of stress mode dependent weighting functions - Mahnken, Rolf; Wilmanns, Stefan (Materials Science and Engineering: A)

Simulation of rate dependent plasticity for polymers with asymmetric effects - Shaban, A.; Mahnken, Rolf; Wilke, L.; Potente, H.; Ridder, H. (International Journal of Solids and Structures)

Simulation of asymmetric effects for shape memory alloys by decomposition of transformation strains - Mahnken, Rolf; Wilmanns, Stefan (Computational Materials Science)

Material Simulation and Damage Analysis at Thermal Shock Conditions - Gockel, Franz-Barthold; Mahnken, Rolf (PAMM)

Simulation of Rate Dependent Plasticity of Polymers - Shaban, Ahmed; Mahnken, Rolf (PAMM)

Simulation of Asymmetric Effects in Plasticity - Mahnken, Rolf (PAMM)

Bessel convolutions on matrix cones - Rösler, Margit (Compositio Mathematica)
Keywords: Algebra and Number Theory

Habermas' Kritik an Bataille: Kommunikation des modernen Subjekts zwischen Zerissenheit und Souveränität - Alpsancar, Suzana
Mit dem „philosophischen Diskurs der Moderne“ versucht Habermas, das Projekt der Aufklärung fortzuführen. Die Kritik an den von ihm so betitelten „Postmodernen“ (Heidegger, Bataille, Derrida, Foucault) dient ihm als Argumentationsgrundlage für die Verteidigung seiner kommunikativen Vernunft. In seiner Prüfung der vermeintlichen Absagen an das Rationale erklimmt seine Konsenstheorie das Siegertreppchen. Die Magisterarbeit diskutiert Habermas’ Kritik an Bataille und entwickelt eine Perspektive jenseits der Dichotomie von „Gut“ und „Böse“.

CHE-Rating: Beschäftigungsfähigkeit (Employability) deutscher Bachelor-Absolventen: Das Fatale daran ist das Fatale darin! - Hertle, Eva; Nordhoff, Daniel; Sloane, Peter F. E.; Sureth-Sloane, Caren (Zeitschrift für Berufs- und Wirtschaftspädagogik)

The Degree of Integrating Corporate and Capital Gains Tax into Income Tax and Its Impact on Investment Decisions - Sureth-Sloane, Caren; Langeleh, Dirk (Schmalenbach Business Review)

Gefährlichkeitseinschätzung von Autofahrern, Motorradfahrern und Radfahrern. Psychometrische Modellierung der Prognose durch verschiedene Gefahrenaspekte und ihr Beitrag zur Klärung von Unterschieden zwischen jungen und nicht-jungen Verkehrsteilnehmern. - Seifert, Andreas

Towards tutoring an interactive robot - Wrede, Britta; Rohlfing, Katharina; Spexard, Thorsten P.; Fritsch, Jannik (Humanoid Robots, Human-like Machines)
Many classical approaches developed so far for learning in a human-robot interaction setting have focussed on rather low level motor learning by imitation. Some doubts, however, have been casted on whether with this approach higher level functioning will be achieved. Higher level processes include, for example, the cognitive capability to assign meaning to actions in order to learn from the tutor. Such capabilities involve that an agent not only needs to be able to mimic the motoric movement of the action performed by the tutor. Rather, it understands the constraints, the means and the goal(s) of an action in the course of its learning process. Further support for this hypothesis comes from parent-infant instructions where it has been observed that parents are very sensitive and adaptive tutors who modify their behavior to the cognitive needs of their infant. Based on these insights, we have started our research agenda on analyzing and modeling learning in a communicative situation by analyzing parent-infant instruction scenarios with automatic methods. Results confirm the well known observation that parents modify their behavior when interacting with their infant. We assume that these modifications do not only serve to keep the infant’s attention but do indeed help the infant to understand the actual goal of an action including relevant information such as constraints and means by enabling it to structure the action into smaller, meaningful chunks. We were able to determine first objective measurements from video as well as audio streams that can serve as cues for this information in order to facilitate learning of actions.

Can Motionese Tell Infants and Robots "What to Imitate"? - Nagai, Yukie; Rohlfing, Katharina (The 4th International Symposium on Imitation in Animals and Artifacts)
An open question in imitating actions by infants and robots is how they know ‘‘what to imitate.’’ We suggest that parental modifications in their actions, called motionese, can help infants and robots to detect the meaningful structure of the actions. Parents tend to modify their infant-directed actions, e.g., put longer pauses between actions and exaggerate actions, which are assumed to help infants to understand the meaning and the structure of the actions. To investigate how such modifications contribute to the infants’ understanding of the actions, we analyzed parental actions from an infant-like viewpoint by applying a model of saliency-based visual attention. Our model of an infant-like viewpoint does not suppose any a priori knowledge about actions or objects used in the actions, or any specific capability to detect a parent’s face or his/her hands. Instead, it is able to detect and gaze at salient locations, which are standing out from the surroundings because of the primitive visual features, in a scene. The model thus demonstrates what low-level aspects of parental actions are highlighted in their action sequences and could attract the attention of young infants and robots. Our quantitative analysis revealed that motionese can help them (1) to receive immediate social feedback on the actions, (2) to detect the initial and goal states of the actions, and (3) to look at the static features of the objects used in the actions. We discuss these results addressing the issue of ‘‘what to imitate.’’

Mittelalterliche Novellistik im europäischen Kontext. Kulturwissenschaftliche Perspektiven. Hrsg. von Mark Chinca, Timo Reuvekamp-Felber und Christopher Young. Berlin: Erich Schmidt Verlag 2006 - Wallmeier, Nadine (Das Mittelalter. Perspektiven mediävistischer Forschung)

Paminas Einweihung. Menschenbild und Geschlechterverhältnisse in der Zauberflöte - Grotjahn, Rebecca (Mozart im Blick: Inszenierungen, Bilder und Diskurse)

Krisenjahre eines Komponisten: Brahms in Detmold 1857–1859 - Grotjahn, Rebecca (ad notam. Jahrbuch der Hochschule für Musik Detmold)

Near-capacity turbo equalization using optimized turbo codes - Trajkovic, Vladimir D.; Fu, Minyue; Schreier, Peter J. (Proc.\ Australasian Telecomm. Netw.\ Applic.\ Conf.)
In this paper we analyze a turbo equalization scheme that combines maximum a posteriori probability (MAP) equalization and turbo decoding. Our aim is to optimize the turbo equalizer in order to approach the information capacity limit for channels with severe inter-symbol interference (ISI). For this purpose, we perform an extensive search for turbo codes that give an SNR-BER performance closest to the channel information capacity limit. Our results show that the optimized turbo equalizer can approach the information capacity limit to within 0.7 dB. We also optimize the turbo equalizer in terms of the minimum number of required turbo decoding iterations. Our results show that a turbo decoder within a turbo equalization loop requires only a small number of iterations. Finally, our analysis reveals that when there are turbo codes with similar extrinsic information transfer characteristics, the computational complexity can be reduced by choosing the code with the smallest constraint length with no loss in SNR-BER performance.

Correlation Coefficients for Complex Random Vectors - Schreier, Peter J. (Proc. 41st\ Asilomar Conf.\ Signals Syst.\ Computers)
We consider the assessment of multivariate association between two complex random vectors. For complex data, there are three types of correlation coefficients, which account for rotational, reflectional, and total (i.e., rotational and reflectional) dependencies. We define and analyze these three types for different correlation coefficients, based on two popular correlation analysis techniques: canonical correlation analysis and multivariate linear regression (also known as half-canonical correlation analysis).

Performance of STBC transmissions with real data - García-Naya, J. A.; Fernández-Caramés, T. M.; Pérez-Iglesias, H. J.; González-López, M.; Castedo, L.; Ramírez, D.; Santamaría, I.; Pérez, J.; Vía, J.; Torres-Royo, J. M. (Proc. IST Mobile $&$ Wireless Comms. Summit)